2015
DOI: 10.1177/0009922815594760
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics for Prevention of Cholangitis in Patients With Biliary Atresia Status Post-Kasai Portoenterostomy

Abstract: Few published studies measure the effect of prophylactic antibiotics after Kasai portoenterostomy. We identified 4 studies and they presented contradictory results. Prospective research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…4,[26][27][28] Despite overall improvements in outcomes, the incidence of cholangitis has changed little over time. [29][30][31][32][33][34][35][36] More than 50% of patients (reported to occur between 40 and 93%, this large difference being probably also the result of different diagnostic criteria) after HPE might present one or more episodes of cholangitis 10,37 ; 31% of patients in our series experienced at least one episode of early perioperative cholangitis. Of note, postoperative care changed during the study period (no steroids since 2011), yet incidence of cholangitis did not change over time.…”
Section: Cholangitismentioning
confidence: 99%
“…4,[26][27][28] Despite overall improvements in outcomes, the incidence of cholangitis has changed little over time. [29][30][31][32][33][34][35][36] More than 50% of patients (reported to occur between 40 and 93%, this large difference being probably also the result of different diagnostic criteria) after HPE might present one or more episodes of cholangitis 10,37 ; 31% of patients in our series experienced at least one episode of early perioperative cholangitis. Of note, postoperative care changed during the study period (no steroids since 2011), yet incidence of cholangitis did not change over time.…”
Section: Cholangitismentioning
confidence: 99%
“…16,21,22 Nevertheless, recent trials and systematic reviews have yielded inconclusive results for determining the effectiveness of prophylactic antibiotics for the prevention of cholangitis after the Kasai portoenterostomy. 19,[22][23][24] In addition, there is no strong evidence that the prolonged use of oral prophylactic antibiotics beyond the early postoperative period offers any greater protection against cholangitis. 5,19,23 Still, most experienced institutions provide oral prophylactic antibiotics for periods of 6 months or longer, similar to the requirements of our hospital's protocol.…”
Section: Discussionmentioning
confidence: 99%
“…19,[22][23][24] In addition, there is no strong evidence that the prolonged use of oral prophylactic antibiotics beyond the early postoperative period offers any greater protection against cholangitis. 5,19,23 Still, most experienced institutions provide oral prophylactic antibiotics for periods of 6 months or longer, similar to the requirements of our hospital's protocol. A randomized control trial by Bu et al 22 found that there was a significantly lower rate of recurrent cholangitis among patients provided with prophylactic antibiotics than that for a historical control group who did not receive antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangitis is the most common complication in BA patients after KPE, the incidence is about 50%~90%. It has reported that varies regimes for prevention of cholangitis in patients with BA after KPE, prophylactic antibiotics after KPE to reduce the incidence of cholangitis is universal, but few published studies provide satisfactory evidence for its benefit [11] . furthermore, the latest research, Wen Bo Pang et al reported that prophylactic imipenem-cilastatin and human immunoglobulin is effectively on the prevention of early-onset cholangitis (12).…”
Section: Discussionmentioning
confidence: 99%